Permasalahan Kriteria Dan Waktu Kerja Pemagangan Berstatus Pelajar (Internship) Dalam Regulasi Ketenagakerjaan Di Indonesia - Sahrul (Zaaken: Journal of Civil and Business Law, 2024)
Problems regarding the exploitation of apprentices with student status in Indonesia still occur frequently, especially in the relationship between employers and apprentices with student status. The purpose of this study is to examine the legal criteria and working hours of Student Apprenticeship (Intership) in Indonesian Labor Regulations. The research uses normative legal research. The results of this study are as follows: First, there is a legal vacuum regarding the criteria for an apprenticeship with Student status (Intership). The criteria for apprenticeship programs regulated in the Labor Law are specifically intended for job training and increased work competency for job seekers who have completed formal studies but are not to reach apprentices who are still students or students. related employment, it does not specifically state how long the working hours are for apprentices but only mentions the duration of the apprenticeship. This means that the determination of working hours is left to each company. The government, with the ministries of manpower and the ministries of education, should coordinate and review regulations related to the implementation of student apprenticeships (Intership) so that they are more effective and provide legal protection for student apprentices. Kata Kunci : kriteria;waktu kerja;Internship;Ketenagakerjaan.